Cholesterol levels determine AChR endocytic route in CHO-K1/A5 cells - Borroni, Maria Virginia (2010)
Stability of the nicotinic acetylcholine receptor (AChR) at the cell surface is critical to the correct functioning of the cholinergic synapse. Cholesterol (Chol) is an essential lipid that modulates AChR levels at the plasmalemma and ion translocation. We have studied the endocytosis of AChR in CHO-K1/A5 cells, a Chinese hamster ovary (CHO) cell line heterologously expressing murine muscle adult-type receptor under different Chol membrane content. Contrary to the norm, endocytosis of cell-surface AChR is accelerated by membrane Chol depletion via a hitherto unknown mechanism. This acceleration is no longer operative when membrane Chol levels are restored. We explored the possible mechanism involved in receptor loss in Choldepleted cells (Chol-). Under such conditions the AChR is internalized by a ligand-, clathrin- and dynaminindependent mechanism, which does not involve the presence of the AChR-associated protein rapsyn. The small GTPase Rac1 is required: expression of a dominant negative form of Rac1, Rac1N17, abrogates receptor endocytosis. At variance with the endocytic pathway in control CHO cells, the accelerated AChR internalization proceeds even upon disruption of the actin cytoskeleton and does not depend on the cytoskeleton-associated inositol lipid PI(4,5)P2; its sequestration by the PH domain of phospholipase C does not alter endocytosis. AChR internalization under Chol- conditions is furthermore found to require the activity of Arf6 and its effectors Rac1 and phospholipase D. Thus, membrane Chol appears to act as a key homeostatic regulator of cell-surface receptor levels, determining the rate and mechanism of AChR endocytosis